Influence of the anastomotic techniques and suture material performing coronary anastomosis on volumetric flow rate - S. Galych; A. Rudenko; E. Nastenko; Y. Starodub (Ukrainian Journal of Cardiovascular Surgery, 2018)
In our study we represent the comparisons of the volumetric blood flow velocities in two groups of coronary anastomoses, which in the first group differed by the technique of suturing, and in the second group – by the diameter of the suture thread. All coronary anastomoses were constructed between porcine vessels. Comparison of the volumetric flow rates through the anastomoses, depending on the technique and suture material, was carried out on the same vascular pairs for maximum purity of the experiment. The results of our investigation revealed that significant differences in the capacity of anastomoses created using different techniques were not observed (p>0.05), while the use of a suture material of smaller diameter (8/0) significantly (p≤0.01) increases the volume flow of blood through the coronary anastomosis up to 10–33% compared to the 7/0 thread and up to 100% compared to the 6/0 filament. Such differences are especially noticeable when grafting coronary arteries of small diameter (≤1.5 mm). Thus, it should be considered that the configurations of coronary anastomoses created by three different methods of suturing are insignificantly different from each other and can equally be used in coronary sur-gery. However, the use of suture material with a thread of smaller diameter (8/0 Prolene) significantly increases the volume velocity of blood flow through the anastomosis and should preferably be used for coronary bypass surgery.